Nocardia cyriacigeogica from Bovine Mastitis Induced In vitro Apoptosis of Bovine Mammary Epithelial Cells via Activation of Mitochondrial-Caspase Pathway - Chen, Wei; Liu, Yongxia; Zhang, Limei; Gu, Xiaolong; Liu, Gang; Shahid, Muhammad; Gao, Jian; Ali, Tariq; Han, Bo (Frontiers in Cellular and Infection Microbiology, 2017)
Nocardia is one of the causing agents of bovine mastitis and increasing prevalence of nocardial mastitis in shape of serious outbreaks has been reported from many countries. However, the mechanisms by which this pathogen damages the bovine mammary epithelial cells (bMECs) is not yet studied. Therefore, this study was designed with the aim to evaluate the apoptotic effects elicited by Nocardia and to investigate the pathway by which the Nocardia induce apoptosis in bMECs. Clinical N. cyriacigeorgica strain from bovine mastitis was used to infect the bMECs for different time intervals, viz. 1 h, 3 h, 6 h, 12 h, and 18 h, and then the induced effects on bMECs were studied using adhesion and invasion assays, release of lactate dehydrogenase (LDH), apoptosis analysis by annexin V and propidium iodide (PI) double staining, morphological and ultrastructural observations under scanning electron microscope (SEM) and transmission electron microscope (TEM), mitochondrial transmembrane potential (ΔΨm) assay using flow cytometry, and the protein quantification of mitochondrial cytochrome c and caspase-9 and caspase-3 by western blotting. The results of this study showed that N. cyriacigeorgica possessed the abilities of adhesion and invasion to bMECs. N. cyriacigeorgica was found to collapse mitochondrial transmembrane potential, significantly (p < 0.05) release mitochondrial cytochrome c and ultimately induce cell apoptosis. Additionally, it promoted casepase-9 (p < 0.01) and casepase-3 (p < 0.05) levels, significantly (p < 0.01) increased the release of LDH and promoted DNA fragmentation which further confirmed the apoptosis. Furthermore, N. cyriacigeorgica induced apoptosis/necrosis manifested specific ultrastructure features under TEM, such as swollen endoplasmic reticulum, cristae degeneration and swelling of mitochondria, vesicle formation on the cell surface, rupturing of cell membrane and nuclear membrane, clumping, fragmentation and margination of chromatin. The present study is the first comprehensive insight into patho-morphological ultrastructural features of apoptosis/necrosis induced by N. cyriacigeorgica, which concluded that the clinical N. cyriacigeorgica induced apoptotic changes in the bMECs through mitochondrial-caspase dependent apoptotic pathway.